Das Handeln von Dritten im athenischen Darlehensrecht des 4. Jahrhunderts v. Chr. (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2022)
The article is attempting to reconsider the intensely discussed topic of how a contract under Greek law was formed by examining the ability of third persons to represent a party to a loan contract in 4th century Athens. A detailed analysis of exemplary sources reveals that the Athenian loan contract was established by the handing over of the loan sum and that also the "giving" or "receiving" of the money by a third person (citizen, non-citizen or slave) led to a contractual obligation of the person who owned the property from which the loan sum originated or who was to benefit from it. Free persons acting as third persons needed either power of disposition over the assets to be bound, for example as asset managers, to be known to the contracting party, or an ad hoc authorisation for the respective transaction. Slaves, as part of the property, acted for its owner anyway.